Social Representations of Suicide in Patients with Suicide Attempt Hospitalized in a Mental Health Institution - Juan Darío Franco-Ramírez; Jorge Luis Cortés Navarro; Gregorio Arturo Hurtado Arango; Julio Andrés Prado Echeverry; Juan Pablo Sierra Gutiérrez; Adriana García Torres (University Library System, University of Pittsburgh, 2023)
BACKGROUND: The suicide rate in the last 45 years has increased considerably in the world, being the frequency of attempted suicide 20 times higher than that of completed suicide. Pereira is one of the cities with the highest rates in the country. METHODS: This qualitative research uses grounded theory as an analysis method, obtaining the data through semi-structured open-type interviews with selective purposive sampling. The analysis of the interviews was done through the grounded theory method and the results are expressed through the theory of social representations. RESULTS: The findings of this research present the discourse of hospitalized patients with suicide attempt. According to social representations, family and derivatives are vital for individual development and their relationship with the environment. Dysfunctions in the family nucleus increase the risk of developing negative thoughts, which can later turn into suicidal behavior. Associated psychiatric pathologies, low self-esteem, relationship problems, sexual abuse and feelings of rejection are risk factors, while study, life projects, and spirituality are protective factors. No relationship was found regarding the consumption of psychoactive substances. CONCLUSION: The family is fundamental in the configuration of the individual and its role as a protective or risk factor in terms of suicide attempt depends on its functionality. It is suggested that work in the families could serve as a strategy for the prevention of the non-fatal suicidal act.